The Variation of Optical Band Gap for ZnO:In Films Prepared by Sol-Gel Technique. (12th December 2013) - Tang, Guomei; Liu, Hua; Zhang, Wei
Abstract : ZnO:In films with different concentrations (0–5 at.%) are successfully synthesized on quartz substrates using sol-gel technique. The structure, morphology, and optical properties of ZnO:In films are investigated by X-ray diffraction, atomic force microscopy, and UV-visible spectrophotometer. It is found that all the films with columnar structural morphology grow along the preferred [001] orientation and the incorporation of indium can improve the crystallinity of ZnO films. The transmittance of the films is about 80% in the visible range. A change of the optical absorption edge from blue shift to red shift is observed for ZnO:In films as the doping concentration increases, which means that the optical band gap first increases and then decreases. The blue shift is due to the Burstein-Moss effect. The sharp jump of the absorption edge from blue-shift to red shift is ascribe to the band gap narrowing caused by the merging of the donor and conduction bands of ZnO:In at high doping concentration.